Ninja future : secrets to success in the new world of innovation - Shapiro, Gary (William Morrow, an imprint of HarperCollinsPublishers, 2019)
In Ninja Future, Shapiro explains the evolving technological landscape, breakthroughs underway now and those we can only envision. New innovations such as self-driving vehicles, blockchain, 5G, the Internet of Things, and countless others will forever change the economy as we know it. Shapiro uses case studies to identify companies and countries addressing todays challenges particularly welland relates lessons from those that have stumbled. Drawing on the insights he has gleaned as a martial arts black belt, he shows how businesses can move to succeed in todays turbulent environment by adopting the mindset of “ninjas”adapting to technological change to capitalize on opportunities at lightning speed.